The profile of people participating in the II International Rally Lovers Narrow Gauge Railway - Barwińska, Sylwia; Gotowski, Rafał; Barwińska-Szczutkowska, Gabriela (Journal of Education, Health and Sport, 2016)
The aim of the research was to identify the profile of people participating in the II International Rally Lovers Narrow Gauge Railway. The study was also intended to check the status of tourism development and the development of information technology, which affect the definition of new ways of advertising. The study was conducted using a questionnaire interview. The research tool was the original questionnaire in the printed version. The research was anonymous and preceded by a pilot study